2023
DOI: 10.1186/s41182-023-00493-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of medicinal plants in Asagirt District, Northeastern Ethiopia

Abstract: Background The people in Ethiopia have developed their own specific knowledge to use, manage and conserve plant resources, giving traditional medicine its diverse nature. Documenting and investigating the traditional and cultural use of remedial plants is vital to extract bioactive chemicals and preserve plant species. This research was conducted with the aim of documenting ethnobotanical and associated knowledge on medicinal plants in Asagirt District, northeastern Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 61 publications
(130 reference statements)
6
20
0
Order By: Relevance
“…Using leaves has less effect on the plant's future survival and the rate of plant tissue regeneration is higher, while using roots, stems and bulbs may mean the destruction of a particular plant species. These findings are in congruence with preceding ethnobotanical studies in Uganda (Nalumansi et al 2014;Tugume et al 2016;) and other parts of the world (Tahir et al 2023) where leaves were reported as the most plant parts used. However, Kefalew et al, (2015) reported that roots are commonly used.…”
Section: Medicinal Plant Parts Used Mode Of Preparation and Administr...supporting
confidence: 91%
See 3 more Smart Citations
“…Using leaves has less effect on the plant's future survival and the rate of plant tissue regeneration is higher, while using roots, stems and bulbs may mean the destruction of a particular plant species. These findings are in congruence with preceding ethnobotanical studies in Uganda (Nalumansi et al 2014;Tugume et al 2016;) and other parts of the world (Tahir et al 2023) where leaves were reported as the most plant parts used. However, Kefalew et al, (2015) reported that roots are commonly used.…”
Section: Medicinal Plant Parts Used Mode Of Preparation and Administr...supporting
confidence: 91%
“…Using a semi-structured interview guide, ethnobotanical data were collected from June 2021 to December 2022, following the International Society of Ethnobiology (2006) guidelines. Demographic information was recorded excluding the name of the herbalist for confidentiality and then field walks were conducted as per the procedure described by Martin (1995) and Tahir et al (2023). Information such as; the appearance of the plants, the local name of the plants, plant part used, mode of preparation, period/frequency of administration, and conservation measures were recorded.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…papaya is a fruit tree that is known for its medicinal uses. It is used in traditional medicine for the treatment of internal parasites and malaria [51,[92][93][94], gastritis [44], jaundice [47], and skin infection [94]. In addition, fresh leaf extract was used to kill insects in local communities in the Korahaye Zone.…”
Section: Carica Papaya L (Caricaceae)mentioning
confidence: 99%